2000
DOI: 10.1136/fn.82.1.f5
|View full text |Cite
|
Sign up to set email alerts
|

International randomised controlled trial of patient triggered ventilation in neonatal respiratory distress syndrome

Abstract: Aim-To compare the eVects of patient triggered ventilation (PTV) with conventional ventilation (IMV) in preterm infants ventilated for respiratory distress syndrome (RDS).Methods-Nine hundred and twenty four babies from 22 neonatal intensive care units were assessed. They were under 32 weeks of gestation and had been ventilated for respiratory distress syndrome (RDS) for less than 6 hours within 72 hours of birth. The infants were randomly allocated to receive either PTV or IMV. Analysis was on an "intention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 33 publications
4
46
0
1
Order By: Relevance
“…New data suggest that our practice to administer bicarbonate in combined acidosis, done to avoid side effects of low pH [19,20] , may have actually reduced the benefi ts of hypercapnia in preventing lung injury [29,30] . Avoiding synchronized ventilation, however, was probably unrelated to the outcomes of this study, as two large randomized trials have failed to demonstrate any outcome benefi t associated with synchronization [21,22] . This study also highlights the diffi culties in achieving high PaCO 2 targets in non-paralyzed preterm infants with moderate lung disease.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…New data suggest that our practice to administer bicarbonate in combined acidosis, done to avoid side effects of low pH [19,20] , may have actually reduced the benefi ts of hypercapnia in preventing lung injury [29,30] . Avoiding synchronized ventilation, however, was probably unrelated to the outcomes of this study, as two large randomized trials have failed to demonstrate any outcome benefi t associated with synchronization [21,22] . This study also highlights the diffi culties in achieving high PaCO 2 targets in non-paralyzed preterm infants with moderate lung disease.…”
Section: Discussionmentioning
confidence: 81%
“…After 7 days, PaCO 2 targets were increased also in the standard ventilation group, in accordance with standard practice in our unit, to hasten extubation. Synchronization was not used, as it has not yet been shown to improve the outcome and therefore was not standard practice in our unit [21,22] . Tidal volumes and dynamic compliance were measured daily in the fi rst 22 randomized patients, as long as they remained intubated, with a CP100 pulmonary function monitor (Bicore Monitoring Systems, Irvine, Calif., USA), which also enabled confi rmation that the auto-PEEP did not occur with our ventilatory strategy.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Different modes of patient-triggered ventilation (PTV), such as SIMV, assist-control, volume limit or volume guarantee, and pressure or volume support ventilation, are widely used in preterm infants. Randomized controlled trials using different modes of PTV have shown short-term benefits such as decrease in the duration of mechanical ventilation or days on oxygen [25,26] . Volume-guaranteed or volume-targeted ventilation results in improved ventilation and stable gas exchange.…”
Section: Invasive Ventilation Via Endotracheal Tubementioning
confidence: 99%
“…Randomized, controlled trails using different modes of PTV have been associated with short-term benefits, such as a decrease in the duration of mechanical ventilation or days on oxygen. 21,22 PTV use was also associated with a decreased need for sedation in VLBW infants. None of these studies demonstrated a significant benefit in terms of reducing lung injury.…”
Section: Introductionmentioning
confidence: 97%